Tax Evasion, Tax Avoidance and Tax Planning in Australia: The participation in mass-marketed tax avoidance schemes in the Pilbara region of Western Australia in the 1990s - Fullarton, Alexander (2009)
This paper will examine the development of mass-marketed tax avoidance schemes in Australia. It will consider changes in approach to tax avoidance from the ‘bottom of the harbour’ schemes of the 1960s and 1970s to the mass-marketed tax avoidance schemes of the 1990s. It will examine the changing structure of tax avoidance from individually crafted tax avoidance structures designed by accountants and lawyers used by high wealth individuals to mass produced structures targeted at highly paid, and therefore highly taxed, blue collar workers in Australia’s mining industry in the 1990s. In the latter half of the twentieth century ‘unacceptable’ tax planning went from highly expensive, individually ‘tailor made’ structures afforded and used only by the very wealthy, to inexpensive replicated structures marketed to skilled and unskilled tradespeople and labourers. By 1998 over 42 000 Australian taxpayers were engaged in tax avoidance schemes with the highest proportion focussed in the mining regions of Western Australia. In the remote and inhospitable mining community of Pannawonica, which has one of the highest paid workforces in Australia, the Australian Taxation Office identified that as many as one in five taxpayers were engaged in a mass-marketed tax avoidance scheme. The paper will identify the causes of these changes, including the advent of the computerised information technology which permitted ‘mass production’ of business structures designed to exploit business incentives in the Australian taxation system in the 1990s. It will also set these developments within the broader context of the tax compliance culture prevailing in Australia and overseas during this period.